An innovative protocol for schwann cells extracellular matrix proteins extraction. Issue 12 (15th August 2016) - Parisi, L.; Zomer Volpato, F.; Cagol, N.; Siciliano, M.; Migliaresi, C.; Motta, A.; Sala, R.
Abstract: The evidence that extracellular matrix (ECM) components could represent new targets for drugs designed to approach degenerative disease, requires their analysis. Before the analysis, proteins should be extracted from ECM and solubilized. Currently, few protocols for ECM proteins extraction and solubilization are available in literature, and most of them are based mainly on the use of proteolytic enzymes, such as trypsin, which often lead to proteins damage. Moreover, no methods have been so far proposed to solubilize Schwann Cell ECM, which may represent an important target for the therapy of neurodegenerative disorders. In our study, we propose to solubilize SC ECM through the use of surfactants and urea. We compared our method of solubilization, with one of that proposed in literature for a general ECM, mainly based on the use of enzymes. We want to highlight the benefit of solubilizing SC ECM, avoiding the use of proteolytic enzymes. To compare the amount of proteins extracted with both methods, MicroBCA assay was used, while the quality of the proteins extracted was observed through the SDS‐PAGE. The results obtained confirm a better solubilization of SC ECM proteins with the proposed protocol, both quantitatively and qualitatively, showing a higher concentration of proteins extracted and a better enrichment of protein fractions, if compared to the enzyme‐based protocol. Our results show that SC ECM could be efficiently solubilized through the use of surfactant and urea, avoiding the use of enzyme‐base methods. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 3175–3180, 2016.